ELEMENTARY SCHOOL STUDENTS' CRITICAL THINKING SKILLS THROUGH FOOD CHAIN LEARNING INDICATORS - Nur Rachmawati Widaya; Farida Istianah; Binar Kurnia Prahani (Universitas Majalengka, 2026)
Natural and Social Sciences (IPAS) learning requires analytical and problem-solving skills through concrete experiences. Problem-solving skills, as part of higher-order thinking, are highly dependent on students' critical thinking skills. This study aims to scientifically analyze the profile of students' critical thinking skills on food chain material at SDN Kwaron 1. This type of research is descriptive quantitative. The research subjects consisted of 23 Phase C students at SDN Kwaron 1. The data collection instruments used written tests to measure critical thinking skills and material comprehension questionnaires. Data analysis techniques were carried out descriptively and quantitatively to provide an objective picture of student achievement. The results showed that students' critical thinking skills were very low. Based on supporting data, 61% of students did not understand the concept of the food chain well. These findings provide empirical evidence of the need to improve critical thinking skills in science education, especially in food chain material in elementary schools.